ANALISIS KEPUASAN MASYARAKAT TERHADAP LAYANAN SIARAN RRI GORONTALO MENGGUNAKAN ALGORITMA C4.5 - Alter Lasarudin; Wahyudin Hasyim (Jurnal Ilmu Komputer (JUIK), 2021)
Radio broadcasting is one of the mass media that is closely related to the needs of the community that can provide various kinds of information, entertainment, and education. Community's satisfaction is the main thing in broadcasting services and becomes a benchmark in improving radio broadcasting services. Sample data used 339 data of respondents. The test results from the model that have been carried out by testing the level of accuracy using the Confusion Matrix, the results of the measurement accuracy are 97.94%, class precision for the satisfaction category is 98.39% and the NOT SATISFIED category is 93.10%. therefore concluded that C4.5 alogarithm can be applied to the process of analyzing public satisfaction with the broadcast service of RRI Gorontalo.